PERENCANAAN REKLAMASI LAHAN BEKAS PENAMBANGAN PIT D1 PT. AMAN TOEBILLAH PUTRA SITE LAHAT SUMATERA SELATAN - Eka Retno Sari; Ansosry Ansosry; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2015)
The steps of the mining activities in PT. Aman Putra Toebillah includes the activities of land clearing, stripping the ground cover, the exploitation of coal, transporting, processing and marketing of coal. After the mining is finished, the ex of mining area will leave an opening hole. Therefore any company of mine obligatory to implement reclamation of ex mining area to maintain environmental sustainability. Based on Ministerial Regulation Number 7 Year 2014, reclamation are activities during of  mining to organize, restore, and improve the quality of the environment and the ecosystem to the function. Therefore, it takes a good planning, so the rate reclamation success can be realized.Mining avtivities include the arrangement of land reclamation. The Inpit Dump will be covered with land cover. Then on the top layer is covered with top soil as a medium growing plants. After the arrangement is finished then the Inpit Dump will be replanting (revegetation). To prevent the erosion, we made waterways, do care and give limes to settling pond to prevent the formation of acid mine water.Based on calculations of planning reclamation and revegetation, direct costs for reclamation activities and revegetation on the Pit D1 PT. Aman Toebillah Putra amount to Rp RP 14.104.226.892,00 and indirect costs amount to Rp 1.339.901.555,00. Then the total cost of reclamation and revegetation on the site amount to Rp 15.444.128.447,00.